2022
DOI: 10.18295/squmj.9.2021.131
|View full text |Cite
|
Sign up to set email alerts
|

The Findings of Pulmonary Nocardiosis on Chest High Resolution Computed Tomography

Abstract: Objectives: Pulmonary nocardiosis is a rare opportunistic infection that is often encountered in immunocompromised patients, in particular those with human immunodeficiency virus (HIV) infection and in solid organ transplant recipients. As the number of immunocompromised patients increase, it is expected that the number of patients with pulmonary nocardiosis will increase. The aim of this study is to review the chest HRCT findings of patients with confirmed pulmonary nocardiosis and to review the imaging featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Imaging studies, such as chest X-rays or CT scans, are critical for evaluating immunocompromised patients with symptoms like dyspnea or altered mental status where there is a suspicion of disseminated disease. Notably, this patient’s imaging did not show typical Nocardiosis findings, such as cavitary or non-cavitary nodules, masses, septal thickening, and centrilobular nodules [ 9 ]. The diagnosis was facilitated by gram staining and culture of joint fluid, as evidenced in Figure 2 , highlighting the importance of these tests for identifying the pathogen and determining its antimicrobial sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies, such as chest X-rays or CT scans, are critical for evaluating immunocompromised patients with symptoms like dyspnea or altered mental status where there is a suspicion of disseminated disease. Notably, this patient’s imaging did not show typical Nocardiosis findings, such as cavitary or non-cavitary nodules, masses, septal thickening, and centrilobular nodules [ 9 ]. The diagnosis was facilitated by gram staining and culture of joint fluid, as evidenced in Figure 2 , highlighting the importance of these tests for identifying the pathogen and determining its antimicrobial sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging manifestations of pulmonary Nocardia spp. infection lack specificity and can be manifested as single or multiple nodules, pulmonary mass (with or without cavity), reticular nodular infiltration, interstitial infiltration, lobar consolidation, subpleural plaque and pleural effusion ( 16 , 17 ). Imaging features like these can easily be misdiagnosed as lung cancer or viral pneumonia ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drug susceptibility testing is particularly important as a guide. Literature data showed that PN is generally effective to sulfonamides antibiotics, and effective to linezolid, imipenem and amikacin ( 16 , 17 ). Antimicrobial susceptibilities for Nocardia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological characteristics of chest CT images in nocardiosis include ground-glass opacities (GGOs), centrilobular nodules, nodules/masses, interlobular septal thickening, bronchial wall thickening, mucoid impaction, cavitation, intralobular reticular opacity, pleural effusion, and enlarged hilar/mediastinal lymph nodes [ 22 , 23 ]. Studies have shown that the most common combination of lung imaging findings in nocardiosis is nodules/masses and interlobular septal thickening (77.8%), while bronchial wall thickening and centrilobular nodules are less commonly observed [ 1 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sputum microbial culture is a repeated, cost-effective, and effective method, but the long culture time may result in delayed diagnosis [ 5 , 23 ]. In addition, the positive rate of bacterial smear and pathological examination of lung tissue remains low.…”
Section: Discussionmentioning
confidence: 99%